1992
DOI: 10.1161/01.atv.12.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with vitamin E but not beta-carotene in vivo protects low density lipoprotein from lipid peroxidation in vitro. Effect of cigarette smoking.

Abstract: Several lines of evidence suggest that oxidatively modified low density lipoprotein (LDL) is atherogenic and that antioxidants may protect LDL against oxidation. In addition, cigarette smoking is known to induce oxidant stress. We have examined the effect of ingestion of the antioxidants D,L-ar-tocopherol (vitamin E) and 0-carotene and of smoking on the resistance of LDL against copper-mediated oxidation. Six healthy nonsmoking volunteers ingested 1,000 IU/day D,L-a-tocopherol acetate for 7 days. After vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
158
4
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(181 citation statements)
references
References 53 publications
16
158
4
2
Order By: Relevance
“…However, we cannot exclude the possibility that carotenoids can moderately in¯uence the lag-time, as there was a signi®cant correlation between all carotenoids and lag-time after supplementation with b-carotene (r 2 0.714, P`0.017; Figure 2). Princen et al, 1992, have reported that any increase in LDL lag-time was observed, despite the massive increase in LDL b-carotene after supplementation. However, these healthy subjects also had a high basal lag-time (100 min) as was shown in this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, we cannot exclude the possibility that carotenoids can moderately in¯uence the lag-time, as there was a signi®cant correlation between all carotenoids and lag-time after supplementation with b-carotene (r 2 0.714, P`0.017; Figure 2). Princen et al, 1992, have reported that any increase in LDL lag-time was observed, despite the massive increase in LDL b-carotene after supplementation. However, these healthy subjects also had a high basal lag-time (100 min) as was shown in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Supplementation with a-tocopherol conferred the increased protection of LDL against in vitro oxidation (Jialal et al, 1995;Reaven et al, 1993). The supplementation with bcarotene did not reveal a substantial improved oxidation resistance after the supplementation (Reaven et al, 1993;Princen et al, 1992). However, in disease states associated with low resistance of LDL to oxidation such as cystic ®brosis, the supplementation with b-carotene resulted in a decrease in oxidation products (MDA) and an increased protection of LDL against in vitro oxidation (Winklhofer- Roob et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking enhances oxidation for example by reducing antioxidant capacity (Dietrich et al, 2003). There are also studies, where a significant association between smoking and decreased lag phase of LDL oxidation was not found (Princen et al, 1992;Marangon et al, 1997).…”
Section: After Vitamin E Supplementationmentioning
confidence: 99%
“…Ex vivo measures of LDL resistance to oxidation have shown significant increases even at low doses of alpha-tocopherol (43-200 mg/day) (Princen et al, 1995;Maskarinec et al, 1999;Upritchard et al, 2003). Antioxidant supplementation or increased consumption of fruit and vegetables has been reported to reduce the susceptibility of LDL to oxidation also in smokers (Princen et al, 1992;Roberts et al, 2003). In fact, beneficial effects of vitamin E supplementation on atherosclerosis may be the most relevant to persons with initially low serum levels of vitamin E. In this study, the lag phase of LDL oxidation prolonged significantly in both the study groups, smokers and nonsmokers after 8 weeks supplementation of vitamin E. Moreover, the effect of vitamin E was greater in smokers than in nonsmokers, which has also been reported by Salonen et al (2003).…”
Section: After Vitamin E Supplementationmentioning
confidence: 99%
See 1 more Smart Citation